ARTIFICIAL INTELLIGENCE AND TERMINOLOGICAL UNITS IN LINGUISTICSTO CHATGPT - Normamatova Zakhro Dilshodovna (Modern American Journals, 2025)
This paper explores the relationship between AI and terminological units in linguistics, analyzing how AI tools contribute to the identification, management, and evolution of specialized terms. The paper discusses the characteristics of terminological units, AI-driven extraction techniques, challenges in computational terminology, and implications for linguistic theory and practice. By integrating insights from terminology science, linguistics, and AI, the study highlights the importance of interdisciplinary collaboration to advance understanding and application of terminological units in the digital age.
Keywords: Artificial intelligence, Terminological units, linguistics, Natural language processing, Terminology extraction, Computational linguistics, Terminology management